Tinjauan Yuridis Empiris terhadap Divergensi Harga Display di Kasir Indomaret dan Alfamart - Hikmawati Sabue; Nur Mohammad Kasim; Dolot Alhasni Bakung (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2023)
This research aims to determine legal protection for consumers regarding differences in display prices at the Indomaret and Alfamart checkout counters. In this research the author uses the type of Juridical-Empirical Law research. Data from the objects studied in this research are classified as primary, secondary and tertiary data. In this thesis, the location where the researcher conducted the research was Gorontalo City, Gorotnalo Province. The choice of research location was based on the consideration that Gorontalo City is the central point for most retail businesses including Alfamart and Indomaret. In this legal research the author uses a statutory approach. The data collection technique was carried out by means of observation and interviews with parties related to the materials studied which were then analyzed using qualitative methods. The results of this research show that in carrying out preventive efforts to protect consumers, the Department of Cooperatives, MSMEs, Industry and Trade (Diskumperindag) of Gorontalo Province carried out several things, such as inspection, counseling and education, and giving warnings or warnings. However, these efforts are not optimal and need improvement, such as inspections that are not regularly scheduled and are often only carried out when receiving complaints from the public, as well as education and counseling which is only carried out to shop owners or employees and less to the public as consumers. Apart from that, researchers also found that preventive efforts to minimize incidents of price display differences were also carried out by Alfamart and Indomaret, such as updating master data, printing price changes as quickly as possible, placing prices on the display accordingly and then changing prices for items that were no longer valid. Regarding repressive efforts, researchers found that in efforts to resolve consumer disputes there are clear regulatory rules and a BPSK institution that handles consumer protection disputes including differences in display prices on Alfamart and Indomaret shelves and cashiers such as mediation, conciliation and legal settlement efforts. However, the problem that arises is the public's ignorance regarding where to complain or report violations as well as the public's negative perception regarding the costs of resolving cases which are considered expensive. To overcome this, researchers believe it is necessary to better educate the public about efficient and affordable complaint and dispute resolution processes.